Analysis Of The Influence Of Group Social Factors, Product Information, Risk Perception And Trust On On Purchasing Decisions (Case Study of Online Shopping Students of the Faculty of Economics, Lamongan Islamic University): Analysis Of The Influence Of Group Social Factors, Product Information, Risk Perception And Trust On On Purchasing Decisions (Case Study of Online Shopping Students of the Faculty of Economics, Lamongan Islamic University) - Noer Rafikah Zulyanti (Institute of Computer Science (IOCS), 2020)
The development of information technology that is very fast including the internet turned out to have a major impact on all aspects that exist, no exception to developments in the business and marketing world. With the rapid development of technology, many people use the technology to make buying and selling transactions using the internet. The purpose of this study is to determine the partial and simultaneous influence between social group variables, product information, risk perception and trust in online purchasing decisions. The study was conducted at the Faculty of Economics, Lamongan Islamic University with a total population of 2300 students. With a simple random sampling and Slovin technique found a sample of 100 respondents. Data collection methods with Kuesionare. Data analysis tools used validity, reliability, multiple regression, coefficient of determination, t test and Test F. The test results found that all research instruments are valid and reliable. Because it is greater than r table and standard reability. Regression test obtained equation Y = 15.148 + 0.707X1 + 0.245X2 + 0.825X3 + 0.139X4. Determination coefficient of 0.591, which means 59 , 1%. While the t test is obtained tCalculate (X1) = 3.101> tTable = 1.994, tCalculate (X2) = 2.266> tTable = 1.994, tCalculate (X3) = 5.401> tTable = 1.994 and tCalculate (X4) = 2.553> tTable = 2.994 1,994 and F test Fcalculate = 8,247> FTabel = 2,49. It is concluded that there is a partial and simultaneous influence between social group variables, product information, risk perception and trust in online purchasing decisions. And the dominant variable is risk perception.